Implicated Subjects in Leila Slimani’s Lullaby: A Transnational Feminist Approach - MAABICH, Omar (Integrated Journal for Research in Arts and Humanities, 2024)
Postcolonialism has been criticized for its binary oppositions, dichotomy, and othering. However, recent postcolonial writers and novelists developed new projects such as Afropolitanism and transnational feminism which have opened new insights and perspectives into the postcolonial disputes and agendas. Leila Slimani’s Lullaby (2018) is a novel that deals with feminist issues par excellence. This study delves into the interconnectedness between transnational feminism and “the Implicate Subjects,” as an approach, to examine the complexity of feminist issues in the novel. The paper tries to unravel how social and cultural norms infiltrate and entangle with discrimination, gender roles, power dynamics, and social-economic inequality that are practiced at the small-scale and large-scale in our contemporary societies. Besides, the intersection between Slimani’s transnational feminism and Rothberg’s Implicated Subjects offers new readings and insights, and bridges connections between Western and non-Western feminism which needs global solidarity and cross-border entanglement.